PENGARUH CAPITAL STRUCTURE DAN SALES GROWTH TERHADAP FINANCIAL PERFORMANCE DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024) - Irvandy Nugraha; Nela Safelia; Riski Hernando (Jurnal Daya Saing, 2026)
Abstract: This study aims to determine the effect of Capital Structure and Sales Growth on Financial Performance, while simultaneously analyzing the role of Firm Size as a moderating variable. The manufacturing sector was selected as the object of observation due to its strategic role in the national economy, where this sector is continuously required to maintain profitability stability amidst fierce market competition and global raw material cost fluctuations. Utilizing a quantitative approach, the research data were sourced from the annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The sample selection method was conducted through a purposive sampling technique, while the relationships between variables were analyzed using Moderated Regression Analysis (MRA) after fulfilling a series of classical assumption tests using SPSS 26. The test results indicate that Capital Structure has no significant effect on Financial Performance, indicating that an excessive reliance on debt financing can burden corporate profitability due to increased interest expenses. However, Sales Growth is proven to have a significant positive effect on driving the improvement of the company's Financial Performance. Regarding the role of Firm Size in this study, the Moderated Regression Analysis demonstrates that this variable acts as a moderator that weakens the impact of Capital Structure on Financial Performance, and strengthens the positive influence of Sales Growth on Financial Performance. These results underscore the importance of efficient debt management and proportional market expansion for financial management. Keywords : Capital Structure, Sales Growth, Financial Performance, Firm Size, Stock Exchange, Moderated Regression Analy